2021
DOI: 10.3390/cancers14010077
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of HPV Positive Tonsillar and Base of Tongue Squamous Cell Carcinomas Reveals a Global Mutational Pattern along with Relapse-Specific Somatic Variants

Abstract: To identify predictive/targetable markers in human papillomavirus positive (HPV+) tonsillar and base of tongue cancer (TSCC/BOTSCC), whole-exome sequencing (WES) of tumours of patients with/without recurrence was performed. Forty primary tumours and adjacent normal tissue were separated by micro-dissection from formalin-fixed paraffin-embedded tissue from patients treated with curative intent 2000–2014 at Karolinska University Hospital. Successful sequencing was obtained in primary tumours of 18 patients witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…We showed that the effect of TRAP150 was enhanced by BCLAF1 (Figure 7D ). In this regard, it is of interest to note that BCLAF1 is mutationally inactivated in ∼40% of HPV-positive tonsillar and base of tongue cancer ( 54 ), suggesting that the absence of BCLAF1 may alter HPV16 E6/E7 mRNA splicing in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the effect of TRAP150 was enhanced by BCLAF1 (Figure 7D ). In this regard, it is of interest to note that BCLAF1 is mutationally inactivated in ∼40% of HPV-positive tonsillar and base of tongue cancer ( 54 ), suggesting that the absence of BCLAF1 may alter HPV16 E6/E7 mRNA splicing in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Kannan et al [34] detected numerous missense mutations in mucin genes, including MUC6 and MUC16, in tonsil samples obtained from HPV-16 positive patients with OPSCC. In addition, Ährlund-Richter et al [35] showed that MUC6 and MUC16 were mutated in over 30% of primary HPV-positive tonsillar squamous cell carcinoma (TSCC) and base of tongue squamous cell carcinoma (BOTSCC) with and without recurrence. In addition, Haft et al [36] found mutations in other mucin genes (MUC4 and MUC5B) in HPV-positive OPSCC patients from The Cancer Genome Atlas database (TCGA).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Haft et al [36] found mutations in other mucin genes (MUC4 and MUC5B) in HPV-positive OPSCC patients from The Cancer Genome Atlas database (TCGA). It has been found that mutated MUC6 and MUC16 were involved in pathways associated with the extracellular matrix and carbohydrates in patients with TSCC and BOTSCC [35]. It was shown that nine out of nineteen mucin genes (including MUC6 and MUC16) were frequently mutated in various cancer types, including HNSCC [37].…”
Section: Discussionmentioning
confidence: 99%
“…To develop personalized medicine for these patients, in order to de-escalate or target treatment, attempts have been made to find prognostic biomarkers, of which many earlier on were defined by immunohistochemistry, and more recently by molecular methodology [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Recently, phosphatidyl-inositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha ( PIK3CA ) and fibroblast growth factor receptor 3 ( FGFR3 ) mutations have frequently been revealed in HPV + TSCC/BOTSCC [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%